(untitled) (Società e diritti, 2020)
The issue of corruption can be considered from multiple points of view, however, by overcoming a strictly legal vision, it is possible to reflect on the anthropology of corruption. The author questions the reasons for spreading a culture of corruption, such as a mentality, a modus operandi, an ethical attitude, a behaviour that produces problems and leads others to evil, a system that starts from the individual interest and there it stops, forgetting every dimension of common good.